An evaluation of human resources development and local government financial information system / Suhairi Suhairi - Suhairi, Suhairi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
The purpose of this research is to analyze the competence of accounting staff in accrual-based accounting and the evaluation of the practice of the Local Government Financial Information System (SIKD-Sistem InformasiKeuangan Daerah) on accrual-based accounting by local governments in West Sumatera, Indonesia. This research shows that the educational background, training and experience influence the competence of accounting staff in implementing accrual-based accounting. The research sample for the evaluation of the accounting staff competence towards accrual-based accounting was the Solok City, the Sawahlunto City, and the South Solok Regency. Research on SIKD was conducted in Solok City, Sawahlunto City, Padang Panjang City, Payakumbuh City and Bukittinggi City as the research sample. Research on accounting staff competence were conducted using a questionnaire while the evaluation of the educational background, training and working experience were performed through in-depth interviews with the relevant officers. It is concluded that the educational background, training and experience positively influence the competence of accrual-basedaccounting. However, the evaluation towards SIKD still shows many weaknesses. The implementation of accrual-based accounting is still at a formality level, and it is not a substantial matter.